Representasi Keanekaragaman Perempuan Indonesia dalam Produk Kosmetik Lokal - Wiraputra, Ardina Lukita; Pristica, Bela (CV. ITTC INDONESIA, 2023)
This article explores the representation of diversity among Indonesian women in local cosmetics products within the framework of